Metacognitive-Discursive Model For Strengthening Critical Reading Of Rural Middle School Students (Journal of Namibian Studies : History Politics Culture, 2022)
The gaps in the inequity of the quality of rural Colombian education prevent students from achieving their expectations for entry into higher education, which demands reflections and research to improve the quality of education in this educational sector.  This article presents the results of an investigation in which the influence of the metacognitive-discursive model on the critical reading skills of 480 rural secondary education students in the department of Córdoba (Colombia) was determined. The quantitative approach with preexperimental design was used with the application of pretest and posttest tests in a related sample, after a model-based intervention. Next, the nonparametric WILCONXON test was applied, which allowed the null hypothesis to be rejected. The results allow us to infer that there is a statistically significant difference between the input and output test, which allows us to conclude that the model allows to strengthen the competences to identify the local contents of the text, to account for its global content and to evaluate the content of the text.